Serum Phosphate Predicts Early Mortality among Underweight Adults Starting ART in Zambia: A Novel Context for Refeeding Syndrome?. (16th April 2013) - Koethe, John R.; Blevins, Meridith; Nyirenda, Christopher K.; Kabagambe, Edmond K.; Chiasera, Janelle M.; Shepherd, Bryan E.; Zulu, Isaac; Heimburger, Douglas C.
Abstract : Background . Low body mass index (BMI) at antiretroviral therapy (ART) initiation is associated with early mortality, but the etiology is not well understood. We hypothesized that low pretreatment serum phosphate, a critical cellular metabolism intermediate primarily stored in skeletal muscle, may predict mortality within the first 12 weeks of ART. Methods . We prospectively studied 352 HIV-infected adults initiating ART in Lusaka, Zambia to estimate the odds of death for each 0.1 mmol/L decrease in baseline phosphate after adjusting for established predictors of mortality. Results . The distribution of phosphate values was similar across BMI categories (median value 1.2 mmol/L). Among the 145 participants with BMI < 18.5 kg/m 2, 28 (19%) died within 12 weeks. Lower pretreatment serum phosphate was associated with increased mortality (odds ratio (OR) 1.24 per 0.1 mmol/L decrement, 95% CI: 1.05 to 1.47; P = 0.01 ) after adjusting for sex, age, and CD4 + lymphocyte count. A similar relationship was not observed among participants with BMI ≥18.5 kg/m 2 (OR 0.96, 95% CI: 0.76 to 1.21; P = 0.74 ). Conclusions . The association of low pretreatment serum phosphate level and early ART mortality among undernourished individuals may represent a variant of the refeeding syndrome. Further studies of cellular metabolism in this population are needed.